Response of weed populations to tillage, reduced herbicide and fertilizer rates in wheat (Triticum aestivum) production - Acciaresi, Horacio Abel (2003)
Field experiments were carried out in 1999 and 2000 to investigate the effects of conventional (CT) and no-tillage (NT) systems, interacting with three herbicide dose levels and three nitrogen (N) levels on weed growth and wheat production of two varieties. There was a higher grain yield for NT system compared with CT in one year. CT weed biomass was lower than from NT weed biomass, in both varieties. No differences on wheat biomass and grain yield were observed between full and reduced herbicide rates. N fertilizer increased wheat biomass and grain yield significantly. Only N medium level had an effect upon weed biomass with respect to non-fertilized plots, while the highest fertilization rate lowered weed biomass. Conventional tillage, reduced herbicide rates and nitrogen fertilization were effective ways of limiting weed production in wheat.